2015
DOI: 10.1523/jneurosci.2579-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Purkinje Cell Simple Spike Encoding of Reach Kinematics during Adaption to a Mechanical Perturbation

Abstract: The cerebellum is essential in motor learning. At the cellular level, changes occur in both the simple spike and complex spike firing of Purkinje cells. Because simple spike discharge reflects the main output of the cerebellar cortex, changes in simple spike firing likely reflect the contribution of the cerebellum to the adapted behavior. Therefore, we investigated in Rhesus monkeys how the representation of arm kinematics in Purkinje cell simple spike discharge changed during adaptation to mechanical perturba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 76 publications
2
46
0
Order By: Relevance
“…Such experiments find that the discharge of SSs sometimes increases rather than decreases after a CS [78][79][80]. These observations are interpreted as evidence that the activity of CSs and SSs is functionally independent and that the mossy fiber→granule cell→parallel fiber→Purkinje cell projection accounts for the modulation of SSs.…”
Section: Alternative Views Of Cerebellar Circuitrymentioning
confidence: 85%
“…Such experiments find that the discharge of SSs sometimes increases rather than decreases after a CS [78][79][80]. These observations are interpreted as evidence that the activity of CSs and SSs is functionally independent and that the mossy fiber→granule cell→parallel fiber→Purkinje cell projection accounts for the modulation of SSs.…”
Section: Alternative Views Of Cerebellar Circuitrymentioning
confidence: 85%
“…However, numerous other studies found no clear relationship between motor errors and CS activity or the discharge of neurons in the inferior olive, the origin of the climbing fiber projection, either during eye or limb movements (see [45]). A very recent study of adaptation of reaching movements to a mechanical perturbation demonstrated that the perturbation evoked a CS response in a very small percentage of Purkinje cells while the simple spike (SS) firing adapted in a majority of the neurons [46]. Also, new findings show that climbing fiber activation occurs and is correlated with changes in SS firing during increases in vestibulo-ocular reflex (VOR) gain but climbing fiber activation does not play a role in modifying SS firing during decreases in VOR gain [47, 48].…”
Section: Do Purkinje Cell Simple Spikes Encode Motor Errors Better Thmentioning
confidence: 99%
“…In the oculomotor vermis, increases in smooth pursuit gain involve increases in velocity coding in the summed Purkinje cell simple spike activity [50, 127]. Therefore, we recently investigated how the representation of kinematics in the simple spike discharge changes during reach adaptation [128]. …”
Section: Simple Spike and Complex Spike Changes During Reach Adaptationmentioning
confidence: 99%
“…The overall weak effect of the perturbation on the complex spike firing can also be appreciated from the population averages. All data are from Hewitt et al [128], with permission…”
Section: Figmentioning
confidence: 99%